Pengaruh Sales Growth, Leverage, dan Deferred Tax Expense terhadap Tax Avoidance (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclical yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Apriyanto, Muhammad Sesar; Purwatiningsih, Purwatiningsih (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to analyze the influence of Sales Growth, Leverage, and Deffered Tax Expense on Tax Avoidance in Non-Cyclical Consumer Sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2018 to 2022. The sampling technique was purposive sampling to obtain a sample as many as 50 companies. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The panel data regression method was used as the research methodology in this study. Analysis of research results using the help of Eviews 12 software. The research results show that simultaneously Sales Growth, Leverage, and Deffered Tax Expense influence Tax Avoidance. Partially, Sales Growth has no effect on Tax Avoidance, Leverage has an effect on Tax Avoidance, and Deffered Tax Expense has no effect on Tax Avoidance.